Dielectric and ferroelectric properties of lead zirconate titanate-lead nickel niobate ceramics under compressive stress - Unruan M. (2014)
Dielectric and ferroelectric properties of complex perovskite lead zirconate titanate-lead nickel niobate ceramic system were investigated under the influence of the compressive stress. The results showed that the dielectric properties, i.e., dielectric constant (εr) and dielectric loss (tan δ), and the ferroelectric characteristics, i.e., the area of the ferroelectric hysteresis (P-E) loops, the maximum polarization (P max), and the remanent polarization (Pr) changed significantly with increasing compressive stress. These changes depended greatly on the ceramic compositions. The experimental results on the dielectric properties could be explained by the deaging phenomenon. The stress-induced domain wall motion suppression and non-180° ferroelectric domain switching processes were responsible for the changes observed for the ferroelectric parameters. In addition, a significant decrease in those parameters after a cycle of stress was observed and attributed to the stress-induced decrease in switchable part of spontaneous polarization. This study clearly showed that the applied stress has significant influence on the electrical properties of complex perovskite ceramics. © 2009 American Institute of Physics.